Seasonal and lactational variations in fatty acid profile of milk in indigenous cattle - MISHRA, GEETESH (The Indian Journal of Animal Sciences, 2022)
The present study was conducted on quality and bioactive components in milk of Kankrej and Sahiwal indigenous cattle breeds at Livestock Research Station, Kodemdesar and College of Veterinary and Animal Science, Bikaner situated in hot-arid region of Rajasthan. Representative milk samples were collected and brought to the laboratory. The variance analysis observed significant effect of season on SFA of Kankrej and Sahiwal, and revealed that the total MUFA in Kankrej differ significantly. Significant effect of season on PUFA in Sahiwal and Kankrej cattle was also observed. Significant effect of season on Omega fatty acids in Sahiwal and Kankrej cattle except Omega-9 fatty acid in Sahiwal cattle was seen. The analysis of variance found highly significant effect of season on SCFA whereas non-significant effect on LCFA in Kankrej and Sahiwal cattle. Effect of season on MCFA was found significant in Sahiwal whereas non-significant effect was found in Kankrej cattle. The analysis of variance observed significant effect of various lactation stage on MUFA, Omega-9 and MCFA fatty acids for Kankrej and Sahiwal cattle and on SCFA in Sahiwal, and non-significant effect in Kankrej whereas significant effect on LCFA in Kankrej and nonsignificant effect in Sahiwal cattle.